2010
DOI: 10.1021/je100163q
|View full text |Cite
|
Sign up to set email alerts
|

Flash-Point Measurements and Modeling for Ternary Partially Miscible Aqueous−Organic Mixtures

Abstract: Flash point is the most important variable used to characterize the fire and explosion hazard of liquids. This paper presents the first partially miscible aqueous−organic mixtures flash point measurements and modeling for the ternary type-I mixtures, water + ethanol + 1-butanol, water + ethanol + 2-butanol, and the type-II mixture, water + 1-butanol + 2-butanol. Results reveal that the flash points are constant in each tie line. Handling the non-ideality of the liquid phase through the use of activity coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…A general model to estimate the flash points of miscible mixtures is reducible for binary aqueous–organic solutions as proposed previously . Another model, developed for partially miscible mixtures, was verified with measured flash point data and is reducible for binary, partially miscible, aqueous–organic solutions . Garland and Malcolm reported that aqueous organic acid mixtures do not flash at a temperature less than 218°F when the water content becomes too high .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…A general model to estimate the flash points of miscible mixtures is reducible for binary aqueous–organic solutions as proposed previously . Another model, developed for partially miscible mixtures, was verified with measured flash point data and is reducible for binary, partially miscible, aqueous–organic solutions . Garland and Malcolm reported that aqueous organic acid mixtures do not flash at a temperature less than 218°F when the water content becomes too high .…”
Section: Introductionmentioning
confidence: 78%
“…The instrument operation met the ASTM D56 standard and employed a closed cup method. The configuration, options, and operation of the flash point analyzer are described in previous studies . The temperature of 50°C was selected as the expected flash point for the first test, and the measured value was used to adjust the expected flash point in the next test.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The operation of the instrument was according to ASTM D56, which is a close cup method. The detailed operational parameters were described in previous studies [3e8, 15,16,25,33,43]. The flash point value of each composition was the average one, measured more than ten times.…”
Section: Flash Point Measurementmentioning
confidence: 99%
“…The main reason maybe attribute to the fact that it costs a lot of manpower, time and material resources to determine the flash points of liquid mixtures by experiment. It may also explain the decision of the EC (European Community) CLP (Classification, Labeling and Packaging) to delay the classification of mixtures until 2015 (Liaw et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%